(untitled) (Texas Journal of Medical Science, 2023)
Treatment for people diagnosed with cancer does not end after the completion of active therapy. The treating physician will continue to check for cancer recurrence, monitor all sorts of side effects, and monitor your overall health. This is called follow-up. It consists of regular medical examinations and tests. Treatment of malignant tumors is accompanied by various side effects. Long-term effects persist after therapy period. Delayed side effects can take months or even years to develop. Long-term and long-term effects can include physical and emotional changes. The standards of medical care for head and neck oncology are the best of modern treatment methods. As one of the treatment options, doctors recommend considering clinical trials. With the help of clinical trials, a new approach to treatment is being tested. Experts want to know if the new treatment is safe and effective. Clinical trials are an option for treatment and cancer care at all stages of cancer. An important factor in treatment is not only the elimination of the tumor, but also the preservation of the functions of the surrounding nerves, tissues and organs. In the treatment of head and neck oncology, the following techniques are used: surgery, radiation, targeted and chemotherapy